A Simulation Analysis of a Multiproduct Multiechelon Inventory-Distribution System - Aggarwal, Sumer C.; Dhavale, Dileep G. (Academy of Management Journal, 1975)
Simulation experiments were conducted to test the overall system response to changes in certain key parameters. The independent variables were demand, lead time, and cost-rate structure. The dependent variables consisted of five management criteria, including average inventory investment and average annual number of reorders within the system.